The use of Ignite (Basta;glufosinate;phosphinothricin) to select transformants of bar-containing plasmids in Neurospora crassa - Martin L. Pall (Fungal Genetics Reports, 1993)
The bacterial Basta-resistance (bar) gene has been previously adapted for use as a fungal selectable marker by Avalos et al. (1989 Curr. Genet. 16:369-372) and by Straubinger et al. (1992 Fungal Genet. Newsl. 39:82-83). Both bialaphos and Basta (Ignite) have been developed for use as herbicides and have only been available as free samples from the chemical companies that have been involved in this development.